The Perceived Risk in Augmented Reality on Students’ Online Purchase Decisions - Thamrin Thamrin; Ika Puspa Satrianny; Nasib Nasib; Ratih Amelia; Wily Julitawaty (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the direct and indirect effects of Augmented Reality (AR) and online trust on online purchasing decisions, with perceived risk as a mediating variable. The study used a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (PLS-SEM). Data were collected from 150 students who had shopped online using AR technology, using a purposive sampling technique. The results of the analysis showed that AR and online trust had a positive and significant effect on online purchasing decisions, and were able to reduce perceived risk. However, perceived risk did not have a significant effect on purchasing decisions, and did not act as a mediator between AR and online trust on online purchasing decisions. These findings indicate that the digital generation is more influenced by interactive experiences and platform credibility than by perceived risk. The managerial implications of this study emphasize the importance of increasing interactive technology and building consumer trust in e-commerce strategies. The research instrument was developed from previously validated indicators, including visual aspects, interactivity, security, and trust in the platform, as well as perceptions of risk and purchasing decisions.